2012
DOI: 10.1089/thy.2011.0248
|View full text |Cite
|
Sign up to set email alerts
|

Graves' Orbitopathy Results in Profound Changes in Tear Composition: A Study of Plasminogen Activator Inhibitor-1 and Seven Cytokines

Abstract: Impaired cytokine balance has been observed in tears of GO patients. Secretion of IL-6 into tears might be a useful indicator of disease activity in GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 53 publications
2
37
3
Order By: Relevance
“…11,28,29 Tear IL-1b, IL-6, and IL-17A levels were higher as CAS increased, indicating that it may be possible to use these cytokines as markers of disease activity. The results also indicated that Th1 cytokines, Th2 cytokines, and Th17 cytokines were involved in the course of TAO.…”
Section: Discussionmentioning
confidence: 99%
“…11,28,29 Tear IL-1b, IL-6, and IL-17A levels were higher as CAS increased, indicating that it may be possible to use these cytokines as markers of disease activity. The results also indicated that Th1 cytokines, Th2 cytokines, and Th17 cytokines were involved in the course of TAO.…”
Section: Discussionmentioning
confidence: 99%
“…Increased dryness symptoms, decreased tear film breakup time, decreased corneal sensitivity, and increased ocular surface staining have been reported both during the active and inactive phases of Graves’ ophthalmopathy [608,609]. Increased tear osmolarity [610,611] and increased levels of inflammatory mediators such as IL-1β, IL-6, IL-8 and plasminogen activator inhibitor-1 have also been found in the tear film of patients with active Graves’ ophthalmopathy [609,612]. …”
Section: Non-pathophysiological Factors Impacting the Tear Filmmentioning
confidence: 99%
“…Serum IL-17 concentration had significant correlation with CAS [146]. Significantly higher PAI-1 [147] and IgE levels [148] were found in TAO patients than in the control groups.…”
Section: Cytokinesmentioning
confidence: 81%